Implementing stroke care in a lower-middle-income country: results and recommendations based on an implementation study within the Nepal Stroke Project - Tunkl, Christine; Paudel, Raju; Bajaj, Sunanjay; Thapa, Lekhjung; Tunkl, Patrick; Chandra, Avinash; Shah, Bhupendra; Karmacharya, Balgopal; Subedi, Ashim; Jalan, Pankaj; Ghimire, Pradesh; Ghimire, Mahesh Raj; et al. (Frontiers in neurology, 2023)
BackgroundGlobally, the majority of strokes affect people residing in lower- and lower-middle-income countries (LMICs), but translating evidence-based knowledge into clinical practice in regions with limited healthcare resources remains challenging. As an LMIC in South Asia, stroke care has remained a healthcare problem previously unaddressed at a national scale in Nepal. The Nepal Stroke Project (NSP) aims to improve acute stroke care in the tertiary healthcare sector of Nepal. We hereby describe the methods applied and analyze the barriers and facilitators of the NSP after 18 months.MethodsThe NSP follows a four-tier strategy: (1) quality improvement by training healthcare professionals in tertiary care centers; (2) implementation of in-hospital stroke surveillance and quality monitoring system; (3) raising public awareness of strokes; and (4) collaborating with political stakeholders to facilitate public funding for stroke care. We performed a qualitative, iterative analysis of observational data to analyze the output indicators and identify best practices.ResultsBoth offline and online initiatives were undertaken to address quality improvement and public awareness. More than 1,000 healthcare professionals across nine tertiary care hospitals attended 26 stroke-related workshops conducted by Nepalese and international stroke experts. Monthly webinars were organized, and chat groups were made for better networking and cross-institutional case sharing. Social media-based public awareness campaigns reached more than 3 million individuals. Moreover, live events and other mass media campaigns were instituted. For quality monitoring, the Registry of Stroke Care Quality (RES-Q) was introduced. Collaboration with stakeholders (both national and international) has been initiated.DiscussionWe identified six actions that may support the development of tertiary care centers into essential stroke centers in a resource-limited setting. We believe that our experiences will contribute to the body of knowledge on translating evidence into practice in LMICs, although the impact of our results must be verified with process indicators of stroke care.